ASSORTMENT POLICY IN THE ENTERPRISE MARKETING SYSTEM - Babukh, Ілона; Zrybnieva, Iryna (Economics and Finance, 2018)
Each enterprise needs an effective assortment policy, which should be the most important component of the enterprise marketing system. When forming the assortment policy, the number of commodity directions in the enterprise, the number of markets for products, the elimination of old or the introduction of new goods, the degree of liquidity are determined. The decisions on the expansion of the product range, expanding the product range down or up the target segments, as well as solutions for the assortment associated with the life cycle of the product are substantiated.
Keywords: marketing; assortment; assortment policy; breadth of product range; expansion of product range; product life cycle